2006
DOI: 10.1016/j.rapm.2006.06.252
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Injection at the Ulnar and the Radial Nerve in Axillary Block Using Triple Stimulation

Abstract: Local anesthetic injection at the ulnar nerve significantly reduces the efficacy and prolongs the onset time of the radial-nerve block when triple-stimulation axillary block is performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
1
2
Order By: Relevance
“…[3][4][5] The authors reported a success rate of 62.9% for median, ulnar and radial sensory block, which is relatively low compared with currently published data (> 92% success rates) and our clinical experience. 6 Despite this discrepancy, the authors conclude that ultrasound "significantly improves the success rate."…”
Section: Ultrasound Guidance and Success Rates Of Axillary Brachial Pcontrasting
confidence: 50%
“…[3][4][5] The authors reported a success rate of 62.9% for median, ulnar and radial sensory block, which is relatively low compared with currently published data (> 92% success rates) and our clinical experience. 6 Despite this discrepancy, the authors conclude that ultrasound "significantly improves the success rate."…”
Section: Ultrasound Guidance and Success Rates Of Axillary Brachial Pcontrasting
confidence: 50%
“…[3][4][5] The authors reported a success rate of 62.9% for median, ulnar and radial sensory block, which is relatively low compared with currently published data (> 92% success rates) and our clinical experience. 6 Despite this discrepancy, the authors conclude that ultrasound "significantly improves the success rate."…”
Section: Ultrasound Guidance and Success Rates Of Axillary Brachial Pcontrasting
confidence: 50%
“…He reported success rates of 93% for median and ulnar sensory block (cold at 30 min) and 95% for the radial nerve. Chan et al 1 accepted triceps rather than distal responses as an appropriate endpoint in 85% of patients despite Sia 5 demonstrating a significant difference in sensory radial nerve blockade when comparing a proximal (triceps) with a distal (wrist/fingers) endpoint (81% vs 95%). The accompanying editorial alluded to the low success rate, but the findings were explained by "rigid definitive endpoints of complete pinprick", and despite stating that the proximal response "may have been detrimental", concluded "clearly, ultrasound visibility of the nerve will enhance success".…”
Section: Ultrasound Guidance and Success Rates Of Axillary Brachial Pmentioning
confidence: 99%